Information Security System Using Blockchain Technology Implementation - Saputra, Tomy; Setiawan, Eko (PT. Riset Press International, 2023)
In today's digital era, information security is a very important thing to pay attention to. There are many methods to maintain information security, but there are still many vulnerabilities that can be exploited by irresponsible parties. Blockchain technology provides a solution by providing a strong and reliable information security system. Blockchain technology can be used to ensure the integrity and validity of stored data. This can be done by storing data in blocks that are connected to one another and using encryption to maintain privacy. In addition, the decentralized system that exists in blockchain technology makes it difficult for irresponsible parties to change or delete it. The application of blockchain technology to information security systems can be carried out in various sectors, such as banking, commerce, and government. In the banking sector, blockchain technology can be used to maintain the integrity of transaction data and ensure that transactions are truly valid. In the trade sector, blockchain technology can be used to ensure that the goods being traded are genuine and have a verifiable source. In the government sector, blockchain technology can be used to store and verify election data, and ensure that election results are truly valid and representative.